pythagoras123
  • pythagoras123
Find C and show your working (steps) \[\frac{C-100}{100}\] = \[\frac{2C-60}{C+60}\]
Mathematics
chestercat
  • chestercat
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

inkyvoyd
  • inkyvoyd
Multiply both sides by 100(c+60)
inkyvoyd
  • inkyvoyd
solve for C, should be a quadratic
inkyvoyd
  • inkyvoyd
C cannot equal -60, becaue that would mean dividing by 0

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

saifoo.khan
  • saifoo.khan
\[\frac{C-100}{100} =\frac{2C-60}{C+60}\]Cross multiply.
saifoo.khan
  • saifoo.khan
\[(C-100) (C+60) = (2C-60)(100)\]Solve.
inkyvoyd
  • inkyvoyd
Foo foo give better answer
inkyvoyd
  • inkyvoyd
But still, make sure C=/=-60
saifoo.khan
  • saifoo.khan
First let him solve @inkyvoyd
inkyvoyd
  • inkyvoyd
I mean, ifthe answer comes out as -60, it won't be accurate, because the denominator is never equal to zero.
anonymous
  • anonymous
(c -100)/100 = (2c-60)/ (c+60) denominator are 100 and c+60 LCM = 100(c+60) multiply both sides with 100(c-60) (c-100)(c+60) = (2c-60)(100) (c-100)(c+60) =c^2 +60c -100c -6000 =c^2 - 40c -6000 (2c-60)(100) =200c -6000 (c-100)(c+60) = (2c-60)(100) c^2 - 40c -6000= 200c -6000 c^2 -40c - 6000 - 200c = 200c -200c-6000 c^2 -240c=0 c(c-240)=0 c=0 or c=240

Looking for something else?

Not the answer you are looking for? Search for more explanations.